Evaluation of Humanity Valuation Education Program in The Elementry School of Insan Teladan Kalisuren Tajur Halang-Bogor - Nugrahanigsih, Valentina Palmarini; Sari, Eliana; Ahmad, Masduki (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study evaluates the humanitarian education program in Kalisuren Exemplary School, Tajur Halang, Parung - Bogor. This study uses an evaluation method with an evaluation model used is the CIPP model which is broken down into Context, Input, Process, and Product with a qualitative approach. Data collection techniques are through observation and interviews. Based on the analysis of the data it was found that the evaluation of humanitarian education programs to get a picture of the effectiveness of learning programs that emphasize human values from the start of input, process, and results. Findings of the results of this study as a whole Humanity Values Elementary Education program for Kalisuren Exemplary Persons, Tajur Halang, Parung - Bogor are under the Guidelines for Conducting Character Education in this case PNK (Humanitarian Value Education), however, there are still success criteria that have been met and partially improved. In detail, the discussion of the results of the evaluation of the Humanitarian Value Education program of Kalisuren Exemplary Elementary School People, Tajur Halang, Parung - Bogor. Humanitarian Value Education is integrated with every subject contained in the curriculum, teaching materials, and thematic learning activities is a quite meaningful approach to integrating human values contained in the learning plans and teaching and learning process. Human Value Education equips people about how to obtain a life filled with love, compassion, helps broaden one's outlook and makes it useful in society and the wider world.